(untitled) (Universal International Scientific Journal, 2026)
This article is about semiconductor materials science, Si- The issues of creating heterostructures based on a cadmium telluride film and obtaining contacts to the created system are considered. The morphology of the obtained coatings, the amount of elements in the coating, their distribution, and the size of polycrystalline particles were studied using modern devices. The change in the voltage-ampere characteristics of the obtained structure depending on the moisture content was studied.